The queen & the spymaster: a novel based on the story of Esther - Rapoport, Sandra E. (Penlight Publications, 2019)
""A novel based on the biblical story of Esther, queen of Persia. The author hews to the ancient text while imagining the suspenseful, gripping, and ultimately triumphant backstory of the unlikely heroes of Xerxes' Persia -- Esther, the Bible's highest-placed sleeper agent, and the shrewd tactician who controls her"--Provided by publisher"--